Science, Religion, and Politics: The Triangulation of Contradictions in Alexis Carrel's Intellectual Legacy - M. A. Sergievsky; E. Yu. Anosova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Research objective: to conduct a comprehensive analysis of Alexis Carrel's (1873–1944) scientific contribution to the development of transplantology and tissue engineering, as well as to investigate his philosophical and social views in the context of the historical epoch of the first half of the 20th century.Tasks: to study in detail Carrel's main scientific achievements in medicine, including the development of the arteriovenous anastomosis method and the creation of an extracorporeal perfusion apparatus. To investigate the controversial aspects of his activities and views, including his attitude towards eugenics.Materials and methods. The study is based on the analysis of Carrel's scientific publications, his book "Man, the Unknown," biographical materials, and historical sources from the first half of the 20th century. Methods of historical analysis, comparative research, and contextual analysis are applied. Archival materials from the Rockefeller Institute for Medical Research and other scientific institutions associated with Carrel's activities are used.Discussion. The article examines the significance of Carrel's scientific discoveries for the development of transplantology. Special attention is given to his work on the arteriovenous anastomosis method, the creation of an extracorporeal perfusion apparatus, and the development of tissue cultivation methods outside the organism. The influence of these achievements on modern organ transplantation protocols is analyzed. Carrel's philosophical and social ideas, as expressed in "Man, the Unknown," are considered in the context of the eugenics movement of the early 20th century. His critique of Western civilization and proposals for "improving" human nature are discussed. A parallel is drawn between Carrel's views and general trends in science and society of that time. The contradictory nature of Carrel's personality as an outstanding scientist and thinker with ambiguous social views is analyzed. His activities during World War II and connections with the Vichy government are examined.Conclusions. Alexis Carrel made a fundamental contribution to the development of transplantology and tissue engineering, laying the foundations for many modern methods and concepts in these fields. His philosophical and social views, including ideas on eugenics, reflected the contradictory tendencies of his time and cannot be evaluated outside of their historical context. Carrel's scientific legacy has had a significant and long-term impact on modern medicine, especially in the fields of transplantology and vascular surgery. Further objective historical assessment of Carrel's activities is necessary, taking into account the full complexity of his personality and the era in which he lived and worked.